Green synthesis of silver nanoparticles from plant latex and their antibacterial and photocatalytic studies. Issue 20 (6th September 2022) - Chandhru, M.; Logesh, R.; Kutti Rani, S.; Ahmed, Neesar; Vasimalai, N.
ABSTRACT: The present work describes a facile synthesis of silver nanoparticles from calotropis procera (CP-AgNPs). The CP-AgNPs were well characterized by many methods. The synthesized CP-AgNPs are stable for more than 5 months. Then we have used CP-AgNPs as photo catalysts for the degradation of methyl orange (MO) dye. The photocatalytic degradation efficiency was 0.0076. Moreover, we also have studied the antibacterial activity against pseudomonas aeruginosa (PA), klebsiella pneumonia (KP), staphylococcus aureus (SA) and bacillus subtilis (BS) bacteria. Interestingly, all four different bacteria causing biofilm were inhibited by CP-AgNPs by 80%. To the best of our knowledge, this is the first report for the synthesis of silver nanoparticles from calotropis procera plant latex. Furthermore, CP-AgNPs effectively were applied as photo catalysts for the degradation of MO dye and also as anti-biofilm agents. GRAPHICAL ABSTRACT: UF0001